The design of WCCS for synchronization web navigation contexts - Wonjoo Park; Sun Joong Kim; Cho Kee Seong; Won Ryu (ICTC 2011, 2011)
Recently, many people are spending most time on web navigation for working, studying by many kinds of smart devices. They also want to continue web navigation services regardless of different devices or browsers. Therefore, we proposed the web collaboration control server(WCCS) to migrate web navigation contexts from one device to other devices. The WCCS is used to move or copy the web navigation contexts including web contents. It is also used to collaborate web contents from many devices.